Different Inhibitory Effects of Erythromycin and Chlortetracycline on Early Growth of Brassica campestris Seedlings - Mi Sun Cheong; Hyeonji Choe; Myeong Seon Jeong; Young-Eun Yoon; Hyun Suk Jung; Yong Bok Lee (MDPI AG, 2021)
Veterinary antibiotics, including erythromycin (Ery) and chlortetracycline (CTC), are often detected in agricultural land. Although these contaminants affect plant growth and development, their effects on crops remain elusive. In this study, the effects of Ery and CTC on plant growth were investigated and compared by analyzing transcript abundance in Brassica campestris seedlings. Treatment with Ery and/or CTC reduced chlorophyll content in leaves and photosynthetic efficiency. Examination of the chloroplast ultrastructure revealed the presence of abnormally shaped plastids in response to Ery and CTC treatments. The antibiotics produced similar phenotypes of lower accumulation of photosynthetic genes, including RBCL and LHCB1.1. Analysis of the transcript levels revealed that Ery and CTC differentially down-regulated genes involved in the tetrapyrrole biosynthetic pathway and primary root growth. In the presence of Ery and CTC, chloroplasts were undeveloped and photosynthesis efficiency was reduced. These results suggest that both Ery and CTC individually affect gene expression and influence plant physiological activity, independently of one another.